Geographical indication for kiwi fruits produced in the southeast of Buenos Aires province, Argentina - Berges, Miriam (2023)
Quality differentiation in food production, including certification of specific standards or attributes, makes possible to obtain better prices and differential access to markets or specific niches of external and domestic demand in medium-high and high incomes segments. These activities usually involve intensive productions, integrated into highly specialized production chains, which imply not only agro-industrial transformations, but also include relatively complex personal and productive services, as well as sophisticated distribution, communication, and packaging channels. Fruit production in the southeast (SE) of Buenos Aires, Argentina, is a labor and capital-intensive activity, generates high profitability in small areas and mobilizes the local and regional economy. Kiwi fruit production in this region has increased steadily over the last ten years in terms of area, volume and infrastructures and recently has incorporated new packaging facilities and cool rooms. The region is the most important and productive zone of kiwi in the country (David et al, 2018). A favorable climate and very suitable soils allow achieving excellent quality fruits and high yields per surface unit.